A cross‐sectional survey of health risk behaviour clusters among a sample of socially disadvantaged Australian welfare recipients. (2nd April 2013) - Bryant, Jamie; Bonevski, Billie; Paul, Chris L.; Lecathelinais, Christophe L.
Abstract: Objective : To examine the prevalence and clustering of six health risk behaviours (smoking, alcohol, inadequate sun protection, physical inactivity, and inadequate fruit and vegetable consumption) among severely disadvantaged individuals. Methods : A cross‐sectional touch screen computer survey was conducted with 383 clients attending a social and community welfare organisation in New South Wales. Participants were assessed on smoking status, alcohol consumption, fruit and vegetable consumption, physical activity, sun protection and socio‐demographic characteristics. Descriptive statistics, factor analysis and logistic regression were used to assess the prevalence, clustering and socio‐demographic predictors of health risk behaviours. Results : Ninety‐eight per cent of the participants reported inadequate vegetable consumption, 62.7% reported inadequate fruit consumption, 82.5% reported inadequate sun protection, 61.7% smoked tobacco, 51.4% consumed alcohol at risky levels and 36.5% were insufficiently active. Most participants (87%) reported three or more risk behaviours. Male participants, younger participants and those with lower education were more likely to smoke tobacco and consume alcohol. Conclusions : The prevalence of health risk behaviours among a sample of typically hard‐to‐reach, severely disadvantaged individuals is extremely high. Implications : Future intervention development should take into account the likelihood of health risk clustering among severely disadvantaged groups.